Karya Seni Poster Shepard Fairey dalam Kajian Semiotika Van Zoest : Analisis Sintaksis, Simantik dan Pragmatik - Adnan Setyoko; Robert Hendra Yudianto (Universitas Bumigora, 2022)
Posters are not only a media for publication and promotion, more than that, posters can be a medium of expression to express the aesthetic and ideological experiences of their creators. Shepard Fairey is a poster artist who is well known in the contemporary art world, especially street art. Shepard Fairey's works display ideas that are full of political and propaganda content. Shepard Fairey's posters feature many themes of peace, anti-war, gender issues, and themes of social criticism. The purpose of this study was to find the symbolic meaning contained in one of Shepard Fairey's works entitled